Differential associations of the stages of pressure and stasis ulcers and social engagement among nursing home residents - Anyah Prasad; Anthony P. Nunes; Bill M. Jesdale; Natalia N. Nielsen; Catherine E. Dubé; Deborah S. Mack; Kate L. Lapane (Aging and Health Research)
Background: Social engagement is an important determinant of health in older adults. Skin ulcers may adversely impact social engagement among nursing home residents. This study sought to quantify the differential associations between pressure and stasis ulcers and social engagement among long-stay US nursing home residents. Methods: Cross-sectional, nationally representative data was obtained from the Minimum Data Set 2.0 on US nursing home residents aged ≥ 50 years with an annual assessment between Oct 1, 2009 and Sept 30, 2010. Adjusted prevalence ratios (aPR) of low social engagement among residents with the four stages of pressure and stasis ulcers and 95 % confidence intervals (CI) were estimated from multivariable Poisson models using a generalized estimating equation approach to account for residents nested within nursing homes. Results: Among the 771,634 residents, 4.5 % had pressure ulcers, and 1.1 % had stasis ulcers. The presence of pressure ulcers, regardless of the stage, was associated with an increased risk of low social engagement (stage 1 aPR: 1.05 (95 % CI: 1.03–1.07); stage 4 aPR: 1.07 (95 % CI: 1.05–1.08)). Residents with stage 1 to 3 stasis ulcers were less likely than those without any skin ulcers to have low social engagement. In contrast, those with stage 4 stasis ulcers had an increased prevalence of low social engagement (aPR: 1.10 (95 % CI: 1.06–1.14)). Conclusion: Social engagement should be monitored and addressed in residents with skin ulcers. Since pressure and stasis ulcers have different etiologies and treatment modalities, they should be considered separately in the empirical work on their association with social engagement.